IMPLEMENTASI PROGRAM PERPUSTAKAAN KELILING DALAM MENINGKATKAN MINAT BACA PESERTA DIDIK DI MA SUNAN SANTRI - Hurin Innihayatus Sa’adah; Ahmad Fatihun Ni’am; Malihatus Sa’diyah; An-nisa’ Khusnul Khotimah; Nur Zuliatin; Tita Aulia Fisabilillah; Sindi Rahmawati; Muhammad Syifaul Umam; Fadilul Musta’an; Faizah Nur Kumila; Novita Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research seeks to examine how the mobile library program was implemented and how it contributed to improving students reading interest at MA Sunan Santri. A descriptive qualitative design was applied on February 11, 2026, involving six primary informants, namely the principal, vice principal, librarian, teachers, PPL students of Universitas Islam Darul ‘Ulum (UNISDA) 2026, and several students. Data were gathered through direct observation, semi-structured interviews, and documentation, then analyzed thematically using the interactive analysis model of Miles, Huberman, and Saldana, supported by source triangulation to enhance data validity. Abstract explain the core of manuscript informatively and obviously including the subject matter proposed approach and solution and show key findings and conclusions. The findings reveal three significant transformations: structural improvement through better access to varied reading materials, behavioral shifts shown by students voluntary engagement in reading activities, and cultural development reflected in collaborative literacy practices within the madrasah. Furthermore, the program strengthened institutional partnership between the madrasah and the university as part of the Tri Dharma of Higher Education. Overall, the mobile library initiative serves not merely as a supplementary literacy service but as a strategic educational intervention that fosters a sustainable literacy-based academic environment and offers a replicable model for similar educational institutions.